Students’ Attitude Toward Active Learning in Health Science Education: The Good, the Challenges, and the Educational Field Differences - Leksuwankun, Surachai; Bunnag, Suwiwat; Namasondhi, Amornrut; Pongpitakmetha, Thanakit; Ketchart, Wannarasmi; Wangsaturaka, Danai; Itthipanichpong, Chandhanee (Frontiers in Education, 2022)
Active learning is an important shift in pedagogical paradigms in recent decades. Previous studies establish many benefits from this learning strategy. However, an implementation is challenging. This study aims to clarify an explanation of the benefits and challenges of active learning from various educational-field students’ perspectives. This study was conducted in a general education course at Chulalongkorn University. Underpinning with a mixed-method study, 22 undergraduates were interviewed in a focus group study. Results were analyzed with deductive thematic analysis and contributed into 23 items in close-ended questionnaires for a cross-sectional quantitative survey study. 222 undergraduates revealed their attitude toward active learning including benefits and challenges. Quantitative data were analyzed with analytical statistics including the Mann-Whitney U test, and these results are supported by thick descriptions derived from qualitative data. An educational theory is also discussed with these results and an educational implication to achieve an effective learning strategy is presented in this study.